Private Activity in Transport Slows Down in 2009, But Remains Concentrated in Road Projects - Izaguirre, Ada Karina; Nicholas, Alexander (World Bank, Washington, DC, 2012)
Private activity in transport declined for the third consecutive year in developing countries. Investments fell by 20 percent and the number of projects dropped by 19 percent in 2009 compared with 2008, according to recently released data from the Private Participation in Infrastructure Database. New private activity in transport was concentrated in road projects, and in a few large developing economies such as Brazil, India, and Mexico. In 2009, 50 transport projects with private participation reached financial or contractual closure in 20 low- and middle-income countries. These projects involved investment commitments of US$19.2 billion. Transport projects implemented in previous years received additional commitments of US$2.5 billion, bringing total investment in 2009 to US$21.7 billion. The private activity was concentrated in the first two quarters of 2009, which accounted for 75 percent of investment in new projects and 64 percent of new projects. Similar concentration occurred in 2008 before the full onset of the global financial crisis. The backlog of projects from the second half of 2008 and the easing of financial constraints in the first half of 2009 (compared with the second half of 2008) may partially explain the concentration of PPI activity in the first half of 2009. Preliminary data suggests that activity by investment and number of projects in the first quarter of 2010 was similar to that reported in the first quarter of 2009.